2021
DOI: 10.1038/s41561-021-00699-z
|View full text |Cite
|
Sign up to set email alerts
|

Current Atlantic Meridional Overturning Circulation weakest in last millennium

Abstract: The Atlantic meridional overturning circulation (AMOC)-one of Earth's major ocean circulation systems-redistributes heat on our planet and has a major impact on climate. Here, we compare a variety of published proxy records to reconstruct the evolution of the AMOC since about 400 AD. Taken together these data presents a fairly consistent picture of the AMOC: After a long and relatively stable period follows an initial decline in the AMOC starting in the 19th Century, with a second, more rapid, decline followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
226
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(241 citation statements)
references
References 13 publications
11
226
3
1
Order By: Relevance
“…Palaeoclimate records suggest that parts of Antarctica and larger parts of Greenland might already have experienced strong ice retreat in the past, especially during the Pliocene as well as during Marine Isotope Stage 5e and 11 (Dutton et al, 2015). It has also been shown that the AMOC experienced a significant slowdown since the mid 20th century (Caesar et al, 2018), which has led to the weakest AMOC state in centuries (Caesar et al, 2021). Models from Phase 5 of the Coupled Model Intercomparison Project (CMIP5) have shown Figure 1.…”
Section: Constraints From Current Observations and Palaeoclimatic Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Palaeoclimate records suggest that parts of Antarctica and larger parts of Greenland might already have experienced strong ice retreat in the past, especially during the Pliocene as well as during Marine Isotope Stage 5e and 11 (Dutton et al, 2015). It has also been shown that the AMOC experienced a significant slowdown since the mid 20th century (Caesar et al, 2018), which has led to the weakest AMOC state in centuries (Caesar et al, 2021). Models from Phase 5 of the Coupled Model Intercomparison Project (CMIP5) have shown Figure 1.…”
Section: Constraints From Current Observations and Palaeoclimatic Evidencementioning
confidence: 99%
“…A more frequent occurrence of El Niño events could have strong impacts on global ecosystems up to a potential dieback of the Amazon rainforest (Duque-Villegas et al, 2019). While some studies have emphasised the uncertainty about future ENSO changes (Kim et al, 2014;Collins et al, 2010), another study found that the frequency of El Niño events could increase twofold in climate change scenarios in sim-ulations of the CMIP3 and CMIP5 climate model ensembles as well as in perturbed physics experiments (Cai et al, 2014). Also, some ENSO characteristics appear to respond robustly to global warming (Kim et al, 2014;Power et al, 2013;Santoso et al, 2013), such as an intensification of ENSO-driven drying in the western Pacific and rainfall increases in the central and eastern equatorial Pacific due to non-linear responses to surface warming (Power et al, 2013).…”
Section: Structural Robustness and Sensitivity Analysis Including Ensomentioning
confidence: 99%
“…These impacts would be magnified and be reached relatively quickly (10-40 years), if a substantial amount of freshwater from Greenland's ice sheets is released into the North Atlantic. In light of recent observations of a substantial ice sheet loss and of the AMOC being currently at its weakest point in millennia 17,18 , our projections provide reasons of major concern for the future of species across major biodiversity hotspots. The effects of global warming and Greenland's melting would be reflected in substantial reductions to species diversity and alteration to species composition.…”
Section: Figures S4 S6)mentioning
confidence: 98%
“…shown that an AMOC regime shift in climate models might necessitate the knowledge of hundreds of years of time series of AMOC variations 50,52 , which is prohibitive with direct observations of it at 26°N that only last for less than 20 years 54 . Here, the reconstruction of our AMV as an internal mode of variability can be related to the internal dynamics of the AMOC through its impact on heat transport and the AMV 13,14,55 . Thus, the change in spectral characteristics of the AMV might be seen as a potential early warning of a regime shift [50][51][52] in the ocean circulation.…”
Section: Unforced Multidecadal Variability and Ongoing Bifurcationmentioning
confidence: 99%